Breakthrough and Collapse in Carl Nielsen’s Sinfonia semplice - Tarrant, Christopher (Danish Yearbook of Musicology, 2017)
The tension between Carl Nielsen’s status as a modernist and his engagement with symphonic form has been a point of sustained scholarly interest in recent years. His Sinfonia semplice (1925) has posed some of the most searching questions for musicologists, formal as well as hermeneutic. Although the work’s title alludes to its straightforwardly conventional layout in four movements and its sometimes childlike thematic materials, the events that occur in the course of the symphony, formal, tonal, and narrative, are far from simple. This article offers a reading of the Sinfonia semplice which draws on Adorno’s categories of ‘breakthrough’ and ‘collapse’, Sonata Theory, and Northrop Frye’s theory of narrative. The denial of straightforwardly heroic or tragic narrative trajectories, I argue, offers further insight into the contribution to interwar modernism that can be found in late Nielsen.